Random Vibration Analysis of RV Reducer based on ANSYS Workbench - Songcheng Xie; Rongsong Yang; Qinghua Zhou (Jixie chuandong)
Taking the RV reducer as the research object， the 3Dmodel of RV reducer is established. Then， it is imported into Adams for kinematic simulation， and the acceleration of spur gear is obtained. The natural frequency of RV reducer is solved by ANSYS Workbench， and then the power spectral density （PSD） function is derived according to the probabilistic statistical analysis technology. Finally， the peak power spectral density is extracted and imported into the Random vibration module of ANSYS Workbench for random vibration analysis. This method considers the influence of random vibration factors on the stress and safety margin of the mechanism， and a new method for solving the reliability problem of RV gear reducer is provided.